Experimental investigation on response characteristics of buried pipelines under surface explosion load. (June 2020) - Tang, Qichen; Jiang, Nan; Yao, Yinkang; Zhou, Chuanbo; Wu, Tingyao
Abstract: In order to study the impact of surface explosion load such as terrorist attacks and disasters on buried pipelines, the field experimental study of the dynamic response characteristics of buried pipelines under surface explosion load was carried out by means of explosion experiment of on-site pre-buried pipelines and explosives, combined with blasting vibration and dynamic strain monitoring. The attenuation law of the ground surface peak particle velocity (PPV) above the pipeline was analyzed under explosion load with varied explosive charge and different blasting distances, meanwhile, the PPV and the peak particle strain (PPS) distribution characteristics of buried pipelines under surface explosion load are studied. The function expression of the relationship between ground surface's PPV, pipeline's PPV and pipeline's PPS is established on the basis of field experiment results. Integrated with the maximum allowable strain theory of pipelines, the safety evaluation of buried pipelines under blasting load is carried out. Then, the "safety area" of explosion parameters for preventing pipeline damage is proposed. Highlights: The field experiments of the full-scale buried pipelines under surface explosion load were carried out. The function expression of the relationship between ground surface's PPV, pipeline's PPV and pipeline's PPS is established. The "safety area" of explosion parameters for preventing pipeline damage is proposed.